Changing models for researching pedagogy with information and communications technologies. (2nd December 2011) - Webb, M.
Abstract This paper examines changing models of pedagogy by drawing on recent research with teachers and their students as well as theoretical developments. In relation to a participatory view of learning, the paper reviews existing pedagogical models that take little account of the use of information and communications technologies as well as those that are focused more specifically on technology‐rich learning environments. A possible framework for understanding pedagogy is beginning to emerge, which can be applied to both face‐to‐face and online learning. This framework combines individual and group regulation of learning where pedagogical reasoning is transparent and shared between students, teachers, and others involved in students' learning. The framework needs to integrate the purposeful elements and sharing of roles characteristic of formative assessment in pedagogy as well as a learning culture that could enable supportive interaction.